Shoulder surgery for tennis players - Gerber, C. (1997)
Even though tennis players often suffer from shoulder injuries, shoulder surgery is rare. Most problems can be overcome by adjusting playing habits and the number of training sessions. The following conditions may require surgery: - Arthropathy of the shoulder joint - Subacromial bursa and superficial layer of supra-spinal tendon - Lesion on the articular side of the capsule of rotating muscles